Profiles of men-who-have-sex-with-men seeking anonymous voluntary HIV counseling and testing at a community-based centre in Malaysia - Koh, Kwee Choy; Kamarulzaman, Adeeba (Malaysian Medical Association, 2011)
Community-based HIV voluntary counseling and testing (VCT) services is an effective alternative for mapping the local demographics of at-risk populations for HIV as well as provide an acceptable and reliable means of early detection of HIV. We describe the profiles of men-who-have-sex-with-men (MSM) who sought VCT services in a community based centre in Kuala Lumpur.